Front Cover: Chemically Diverse S. mansoni HDAC8 Inhibitors Reduce Viability in Worm Larval and Adult Stages (ChemMedChem 3/2023). (3rd February 2023) - Noce, Beatrice; Di Bello, Elisabetta; Zwergel, Clemens; Fioravanti, Rossella; Valente, Sergio; Rotili, Dante; Masotti, Andrea; Salik Zeya Ansari, Mohammad; Trisciuoglio, Daniela; Chakrabarti, Alokta; Romier, Christophe; Robaa, Dina; et al.
Abstract : The Front Cover shows how Neglected Tropical Diseases including schistosomiasis don′t have effective strategies to fight the parasite infection. Only a few drugs for treating such diseases display selectivity against parasites over humans, and only some of them exhibit activity against all the parasite stages of life. In schistosomiasis, for example, Praziquantel displays effective action against adult worms but not against larvae and the juvenile forms. In this study, a small library of histone deacetylase (HDAC) inhibitors exhibited submicromolar/nanomolar potency against S. mansoni HDAC8 (smHDAC8) and diverse degrees of selectivity over human HDAC1 and/or HDAC6. Thus, just as in the case of the seemingly impossible to solve Rubik′s cube, the use of smHDAC8‐selective inhibitors could open the door to new innovative drugs against schistosomiasis. Cover design by Dr Beatrice Noce and Dr Elisabetta Di Bello. More information can be found in the Research Article by Beatrice Noce, Antonello Mai et al.